Analisa Kebutuhan Beban Pendingin Untuk Aula Kampus III UM Sumatera Barat - Riza Muharni; Fajar Nur Fadhli; Muchlisinalahuddin Muchlisinalahuddin (Politeknik Negeri Padang, 2022)
The comfort factor of a room is determined according to the location, characteristics and activities in the room. In order for the room to feel comfortable, a tool is needed to cool the room. The hall of Campus III UM West Sumatra as a place for academic activities measuring 28.3 m long, 8.3 m wide, 3.2 m high with a capacity of 130 people, requires air conditioning according to the needs of the room. This study aims to determine the need for air conditioning cooling load for the hall space. The research carried out literature review and observation, calculating temperature, temperature, hall size, and others. The result of the research is that the cooling load is 25.44 kW, so 3 units of split PK type AC are needed